Surreal visual discourse in graphic design (poster sample) (Journal of the College of Basic Education, 2022)
Art in general and design in particular has been affected by intellectual changes and transformations of aesthetic and visual visions and the philosophy of their analysis, which change according to a rapid movement that knows no boundaries of time, and those transformations transcend the boundaries of places. The typographic design has undergone clear-cut influences of various schools of art, especially plastic ones, such as abstraction, cubism and surrealism.